Bonding paste and bonded body

The bonding paste, formulated with specific metal particles and a dispersion medium, addresses the challenge of achieving high thermal conductivity and bonding strength under pressure-free conditions for large-area SiC devices, while maintaining bonding integrity during thermal cycles.

JP7666578B1Active Publication Date: 2025-04-22TOYO INK MFG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023221139
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-04-22
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

Existing bonding materials struggle to achieve high thermal conductivity and bonding strength under pressure-free conditions, while also maintaining bonding strength during cold and heat cycles, especially for large-area SiC devices.

Method used

A bonding paste composed of metal particles with specific average particle diameters and a dispersion medium, which includes terpene and glycol ether systems, is used. This paste suppresses voids in the coating film after sintering, achieving high thermal conductivity and excellent bonding strength without the need for pressure.

Benefits of technology

The bonding paste effectively reduces voids and enhances thermal conductivity and bonding strength, even under pressure-free conditions, while maintaining bonding strength during cold and heat cycles, thus addressing the limitations of existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666578000001
    Figure 0007666578000001
  • Figure 0007666578000002
    Figure 0007666578000002
  • Figure 0007666578000003
    Figure 0007666578000003
Patent Text Reader

Abstract

Provided is a bonding paste that suppresses voids in a coating film after sintering even under pressure-free conditions, exhibits high thermal conductivity, has excellent bonding strength, and can suppress a decrease in bonding strength due to thermal cycles; and provides a bonded body using the bonding paste. [Solution] The above problem is solved by a joining paste containing metal particles (A) and a dispersion medium (B), in which the metal particles (A) contain 50 mass% or more of metal particles (a) having an average particle diameter of 100 nm or more and 500 nm or less, based on the total mass of the metal particles (A), and when the joining paste is heated at a heating rate of 3°C / min, and the weight loss at 200°C, M200, is 88 or more and 98 or less, assuming that the weight loss at 650°C, M650, is 100.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a bonding paste that has excellent thermal conductivity and bonding strength under non-pressure conditions and can suppress a decrease in bonding strength due to thermal cycles, and a bonded body using the bonding paste. [Background technology]

[0002] Conventionally, solder has been used as a bonding material for bonding metal members together, between a metal member and a semiconductor element, between a metal member and a light-emitting diode (LED) element, etc. In recent years, in the technical field of next-generation power electronics, devices such as SiC capable of operating at high temperatures are in demand. As a bonding material for manufacturing such devices, a substitute material for solder is in demand from the viewpoint of high-temperature operation reliability, and for example, as shown in Patent Documents 1 and 2, bonding materials such as bonding paste using sinterable metal particles have been proposed.

[0003] Patent Document 1 discloses a bonding material containing metal nanoparticles and a solvent, in which the values ​​of heat loss at 100°C, 150°C, and 200°C are specified, with the heat loss L700 when the material is heated from 40°C to 700°C at a heating rate of 3°C / min in a nitrogen atmosphere being taken as 100%. Patent Document 2 discloses a bonding composition that contains inorganic particles and a specific organic substance attached to at least a portion of the surface of the inorganic particles, and whose weight loss rates when heated from room temperature to 200°C and when heated from 200°C to 300°C are specified by thermal analysis. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-164895 A [Patent Document 2] International Publication No. 2013-061527 Summary of the Invention [Problem to be solved by the invention]

[0005] There are two types of bonding processes using such bonding materials: a method performed without pressure (hereinafter referred to as pressureless bonding) and a method performed under pressure (hereinafter referred to as pressure bonding). Pressure bonding is effective in reducing voids, improves thermal conductivity, and promotes sintering of metal particles, making it possible to form strong bonds, and has the advantage of excellent bond strength and thermal cycle properties. However, pressure bonding requires dedicated equipment, and the objects to be bonded must be able to withstand a pressurized environment, so the objects to be bonded and their applications are limited. For this reason, there is a demand for pressureless bonding to reduce voids and achieve high thermal conductivity, as well as to achieve strong bonds and improve bond strength and thermal cycle properties. On the other hand, in recent years, the area of ​​semiconductor elements has been increasing, but it is known that the larger the area of ​​the element, the more difficult it is for gases and the like inside to escape, and voids tend to occur. In addition, the difference between the linear expansion coefficient of Si elements and SiC elements and the linear expansion coefficient of copper used as silver particles and base material is very large, and during a thermal cycle test, distortion occurs between the copper base material / bonding layer containing silver particles / Si or SiC element layers, which tends to cause cracks and reduce thermal cycle characteristics. Furthermore, although the linear expansion coefficient of SiC elements is about the same as that of Si elements, the hardness is higher than that of Si elements, so that the distortion during thermal cycles is larger than that of Si elements, and cracks tend to occur in the bonding layer. That is, the level of requirements for improving the bonding strength and thermal cycle characteristics of SiC semiconductor elements has been increasing in recent years.

[0006] However, the inventions described in Patent Documents 1 and 2 do not satisfy the constituent elements of the present invention, and cannot solve the problems of bonding strength and thermal cycle characteristics when large-area SiC elements are bonded without pressure.

[0007] Therefore, the problem that the present disclosure aims to solve is to provide a joining paste that suppresses voids in a coating film after sintering even under pressure-free conditions, exhibits high thermal conductivity, has excellent joining strength, and can suppress a decrease in joining strength due to thermal cycles, and a joined body using the joining paste. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved. [1]: A joining paste comprising metal particles (A) and a dispersion medium (B), the metal particles (A) containing metal particles (a) having an average particle diameter of 100 nm or more and 500 nm or less, in an amount of 50 mass% or more based on the total mass of the metal particles (A), and wherein, when the joining paste is heated at a heating rate of 3°C / min, the weight loss at 200°C, M200, is 88 or more and 98 or less, where M650, the weight loss at 650°C, is taken as 100. [2]: The joining paste according to [1], wherein when the weight loss M650 is taken as 100 and the weight loss at 150°C is taken as M150, the ratio of the weight loss M150 to the weight loss M200 (M150 / M200) is 0.975 or more. [3]: The joining paste according to [1] or [2], wherein the content of the dispersion medium (b1) having a boiling point of 250°C or more and 300°C or less in the dispersion medium (B) is 50 mass% or more based on the total mass of the dispersion medium (B). [4]: The bonding paste according to [3], wherein the dispersion medium (b1) contains at least one selected from the group consisting of terpenes and glycol ethers. [5]: The joining paste according to any one of [1] to [4], wherein the content of the dispersion medium (B) having a boiling point exceeding 300°C is 10 mass% or less based on the total mass of the dispersion medium (B). [6]: The joining paste according to any one of [1] to [5], wherein the content of the dispersion medium (B) having a hydroxyl group is 90 mass % or more based on the total mass of the dispersion medium (B). [7]: A bonded body in which a first bonded part and a second bonded part are bonded by the bonding paste according to any one of [1] to [6]. [8]: The bonded body according to [7], wherein the first bonded portion is an untreated substrate. [9]: The joined body according to [7] or [8], wherein the second joined portion is made of SiC. Effect of the Invention

[0009] The present invention can provide a bonding paste that suppresses voids in a coating film after sintering even under pressure-free conditions, exhibits high thermal conductivity, has excellent bonding strength, and can suppress a decrease in bonding strength due to thermal cycles, and a bonded body using the bonding paste. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The bonding paste of the present disclosure is a bonding paste containing metal particles (A) and a dispersion medium (B), wherein the metal particles (A) have a ratio of metal particles (a) having an average particle diameter of 100 nm or more and 500 nm or less of 50 mass % or more, and wherein, when the bonding paste is heated at a heating rate of 3°C / min, the weight loss M650 at 650°C is taken as 100, and the weight loss M200 at 200°C is 88 to 98. The bonding paste of the present disclosure contains 50 mass% or more of metal particles (A) having an average particle size of 100 nm or more and 500 nm or less, and the ratio of the weight loss M200 at 200°C to the weight loss M650 at 650°C is within a predetermined range. Therefore, even under strict bonding conditions of no pressure and when the members to be bonded are untreated substrates such as plating-less substrates or SiC semiconductor elements, for which stable bonding is difficult, the bonding paste can exhibit excellent bonding strength and bonding strength after thermal cycles. In particular, the present invention provides a bonding paste that has high thermal conductivity, high bonding strength at the bonded portion, and suppresses a decrease in bonding strength due to thermal cycles, and that can be bonded without pressure, and a bonded body using the bonding paste. In addition, the present invention provides a bonded body using the bonding paste that can exhibit high thermal conductivity, excellent bonding strength, and thermal cycle characteristics even when a large-area SiC element is bonded without pressure.

[0011] <Metal particles (A)> The metal particles (A) exert the electrical conductivity and thermal conductivity of the bonded body and play a role in bonding the bonded bodies during the sintering process, and include silver, copper, alloys containing silver and / or silver, silver oxide, copper oxide, and coated particles in which a core body made of a metal (excluding silver and copper) is coated with silver and / or silver. By using the metal particles (A), a bonded body having excellent strength can be obtained. In addition, the metal particles (A) can be used at a wide range of firing temperatures and in various firing environments such as atmospheric pressure, nitrogen atmosphere, vacuum, or reducing atmosphere.

[0012] Metal particles (A) contain a specified amount or more of metal particles (a) (hereinafter referred to as metal particles (a)) with an average particle size of 100 nm or more and 500 nm or less, and exhibit the function of melting or bonding (hereinafter also referred to as sintering) the particles to each other in the temperature range of 200°C to 350°C where the joining paste is heated and sintered, and become capable of changing into bulk metal. As a result, the objects to be joined are joined. Hereinafter, the portion formed by sintering the metal particles (A) present between the objects to be joined is referred to as the joining layer. From the viewpoints of electrical conductivity and thermal conductivity, the metal particles (A) and the metal particles (a) are preferably particles using silver or copper, and from the viewpoint of oxidation resistance, they are more preferably silver particles.

[0013] In the present disclosure, it is important that the metal particles (A) contain 50% by mass or more of metal particles (a) having a specific average particle size. In this specification, the term "average particle size" means the 50% cumulative particle size distribution particle size (d50) on a volume basis determined by the measurement method described in the Examples. The d50 of the metal particles (a) is 100 nm or more and 500 nm or less, preferably 150 nm or more, and more preferably 200 nm or more. In addition, the d50 of the metal particles (a) is preferably 400 nm or less, and more preferably 300 nm or less.

[0014] The metal particles (A) and the metal particles (a) may have their surfaces coated with an organic component. For example, the silver particles (A) and the silver particles (a) may be particles in which the surfaces of the silver particles are coated with an organic component. The organic component is also called a protective agent. When the silver particles are coated with an organic component, the storage stability of the bonding paste is improved. Examples of the organic component include fatty acids, aliphatic amines, aliphatic alcohols, etc., and saturated or unsaturated fatty acids are preferred, saturated or unsaturated fatty acids having 3 to 18 carbon atoms are more preferred, and saturated or unsaturated fatty acids having 6 to 18 carbon atoms are even more preferred. The organic component may contain one or more types.

[0015] The content of metal particles (a) having a specific average particle size in the metal particles (A) is preferably 70 mass% or more, more preferably 85 mass% or more. The metal particles (A) and the metal particles (a) may each be independently used alone or in combination. The metal particles (A) may contain metal particles other than the metal particles (a) within a range that does not impair the effects of the present invention. The metal particles (A) may contain metal particles having an average particle diameter of more than 500 nm, may be combined with metal particles having an average particle diameter of more than 1000 nm, or may be different metal species.

[0016] <Dispersion medium (B)> The bonding paste of the present disclosure contains a dispersion medium (B). The dispersion medium (B) serves to disperse the metal particles (A) and to impart fluidity to the coating film in the silver sintering process. Examples of the dispersion medium (B) include terpineol, dihydroterpineol, dihydroterpinyl acetate, Tersolve TOE100, Tersolve MTPH (manufactured by Nippon Terpene Co., Ltd.), Texanol (2,2,4-trimethylpentane-1,3-diol monoisobutyrate), carbitol, carbitol acetate, butyl carbitol, isophorone, γ-butyl lactone, dipropylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol methyl-n-propyl ether, 3-methoxy-3-methylbutyl acetate, ethylene glycol, propylene glycol diacetate, and dipropylene glycol methyl ether acetate. Examples of the dispersing medium include isoparaffin-based dispersing mediums contained in hydrocarbon-based dispersing mediums, and these may be used alone or in combination of two or more.

[0017] The dispersion medium (B) preferably contains 50% by mass or more of a dispersion medium (b1) (hereinafter referred to as dispersion medium (b1)) having a boiling point of 250°C or more and 300°C or less, based on the total mass of the dispersion medium (B). By containing 50% by mass or more of the dispersion medium (b1), the dispersion medium is more likely to remain in the silver sintering process, and it becomes easy to set the weight loss M200 value at 200°C to 88 or more and 98 or less. The content of the dispersion medium (b1) is preferably 60% by mass or more, more preferably 70% by mass or more, based on the total mass of the dispersion medium (B). The boiling point of the dispersion medium (b1) is preferably 260°C or more.

[0018] In addition, the dispersion medium (B) preferably contains 10 mass % or less of a dispersion medium (b2) (hereinafter referred to as dispersion medium (b2)) having a boiling point exceeding 300°C, based on the total mass of the dispersion medium (B). By containing 10 mass % or less of the dispersion medium (b2), the dispersion medium does not remain excessively in the silver sintering step, and it becomes easy to set the weight loss M200 value at 200°C to 88 or more and 98 or less. If the weight loss M200 value at 200°C is 88 to 98, the dispersion medium remains at the sintering stage, increasing the fluidity of the coating film and suppressing the generation of voids in the coating film after sintering, allowing high thermal conductivity to be exhibited. In addition, the wettability of the joint to the parts to be joined is improved, increasing the contact area, allowing for the formation of a strong joint. This allows for excellent joint strength and thermal cycle resistance.

[0019] Examples of the dispersion medium (b1) having a boiling point of 250° C. or more and 300° C. or less include terpenes such as Tersolve TOE-100 (2-(1-methyl-1-(4-methyl-3-cyclohexenyl)ethoxy)ethanol) (manufactured by Nippon Terpene Chemical Co., Ltd.); glycol ethers such as diethylene glycol monohexyl ether, triethylene glycol monoethyl ether, and triethylene glycol monobutyl ether; Texanol (2,2,4-trimethylpentane-1,3-diol monoisobutyrate) and 1,6-diacetoxyhexane. Among them, at least one selected from the group consisting of terpenes and glycol ethers is preferably used.

[0020] The dispersion medium (B) preferably contains a dispersion medium containing a hydroxyl group. When the dispersion medium (B) has a hydroxyl group, it is adsorbed to the metal particles (A) and the dispersibility is improved. Furthermore, the evaporation of the dispersion medium is slowed down, so that the film shrinkage that occurs during sintering is slowed down. This increases the fluidity of the coating film, suppresses the generation of voids in the coating film after sintering, and exhibits high thermal conductivity. In addition, the wettability to the bonded parts is improved and the contact area is increased, so that a strong bond can be formed. This allows the bonding strength and thermal cycle resistance to be excellent. From the above viewpoints, the content of the hydroxyl group-containing dispersion medium is preferably 90 mass % or more, and more preferably 95 mass % or more, based on the total mass of the dispersion medium (B).

[0021] Examples of dispersion media containing hydroxyl groups include terpineol-based media such as terpineol, dihydroterpineol, dihydroterpinyl acetate, Tersolve TOE-100 (2-(1-methyl-1-(4-methyl-3-cyclohexenyl)ethoxy)ethanol), and Tersolve MTPH (isobornylcyclohexanol); and glycol ether-based media such as diethylene glycol monohexyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, and polyethylene glycol monobutyl ether.

[0022] <Weight reduction> As described above, it is important that the bonding paste of the present disclosure has a weight loss M200 of 88.0 or more and 98.0 or less when the weight loss M650 at 650°C is taken as 100 when the temperature is increased at a heating rate of 3°C / min. If the weight loss M200 is within the above range, the dispersion medium remains at the sintering stage, so that the fluidity of the coating film is increased, and the generation of voids in the coating film after sintering is suppressed, and high thermal conductivity can be exhibited. In addition, the wettability to the bonded parts is improved and the contact area is increased, so that a strong bond can be formed. This allows the bonding paste to exhibit excellent bonding strength and thermal cycle resistance. When M650 is taken as 100, the value of M200 is preferably 90.0 or more and 96.0 or less. In this specification, when the weight loss at 650°C, M650, is taken as 100, the weight losses at 150°C, 250°C and 300°C are taken as M150, M250 and M300, respectively. The weight loss can be measured using thermogravimetric differential thermal analysis (hereinafter also referred to as TG-DTA analysis). For example, a thermogravimetric differential thermal analyzer (TG / DTA8122 (manufactured by RIGAKU)) is used, and 10 mg of a sample is heated in a nitrogen atmosphere at a heating rate of 3°C / min, with a starting temperature of 30°C.

[0023] From the viewpoints of the thermal conductivity, bonding strength, and thermal cycle characteristics described above, the joining paste of the present disclosure may have an M150 of 85.0 or more and 96.0 or less, an M250 of 93.0 or more and 98.5 or less, and an M300 of 96.0 or more and 99.0 or less.

[0024] In addition, the bonding paste of the present disclosure preferably has a ratio of M150 to M200 (M150 / M200) of 0.975 or more. By setting the value of M150 / M200 to 0.975 or more, the rapid volatilization of the dispersion medium and other organic substances is suppressed during the sintering process between 150°C and 200°C, and the shrinkage of the coating film that occurs during sintering is gradual. This increases the fluidity of the coating film, suppresses the generation of voids in the coating film after sintering, and exhibits high thermal conductivity. In addition, the wettability to the bonded parts is improved and the contact area is increased, thereby forming a strong bond. This allows the bonding strength and thermal cycle resistance to be excellent.

[0025] From the viewpoints of the thermal conductivity, bonding strength, and thermal cycle characteristics described above, the joining paste of the present disclosure may have a ratio of M200 to M250 (M200 / M250) of 0.95 or more, and a ratio of M150 to M250 (M150 / M250) of 0.93 or more.

[0026] <Compound (C)> The bonding paste of the present disclosure may contain a compound (C) (hereinafter referred to as compound (C)) having 20 to 80 carbon atoms and having two or more functional groups (c) selected from the group consisting of hydroxyl groups, carboxy groups, and amino groups. By containing such a compound (C), the composition can exist as a liquid composition even after a part or all of the dispersion medium (B) has evaporated, so that a good bonding interface integrated with the parts to be bonded can be formed. In addition, each functional group (c) has high binding ability with metal particles and exhibits excellent dispersibility. The number of carbon atoms in compound (C) includes the number of carbon atoms in functional group (c). Therefore, when functional group (c) in compound (C) is a carboxy group, the number of carbon atoms in the carboxy group is also included in the number of carbon atoms in compound (C).

[0027] In the compound (C), the skeleton (partial structure) excluding the functional group (c) is an organic residue, but is preferably a hydrocarbon group or a group in which multiple hydrocarbon groups are bonded with a linking group containing a hetero atom. Examples of such linking groups containing a hetero atom include -O- group (ether group), -C(=O)- group (carbonyl group), -C(=O)-O- group (ester group or oxycarbonyl group), and -C(=O)-NH- group (amide group or iminocarbonyl group). It is preferable that the compound (C) does not have any functional group other than the functional group (c).

[0028] When the number of functional groups (c) in compound (C) is n, compound (C) preferably has an n-valent hydrocarbon group. In compound (C), the skeleton excluding functional groups (c) is more preferably composed of only n-valent hydrocarbon groups, in that a strong bonded body can be obtained.

[0029] The number of functional groups (c) in the compound (C) is preferably 2 or 3. The compound (C) may have a linear structure or a branched and / or cyclic structure, but preferably has a branched and / or cyclic structure. When the compound (C) has a branched and / or cyclic structure, it is preferable that the compound has a branched and / or cyclic structure, since the compound has low crystallinity and is likely to become a liquid having good fluidity.

[0030] Examples of the compound (C) having a linear structure include eicosane diacid, heneicosane diacid, docosane diacid, tetracosane diacid, triacontanedioic acid, dotriacontanedioic acid, tetracontanedioic acid, pentacontanedioic acid, hexacontanedioic acid, and batyl alcohol. Examples of the compound (C) having a branched and / or cyclic structure include dimer acid, trimer acid, tetramer acid, dimer diol, trimer triol, tetramer tetraol, dimer diamine, trimer triamine, tetramer tetramine, and phytantriol. The compound (C) is more preferably a compound selected from the group consisting of dimer acid, trimer acid, dimer diol, trimer triol, dimer diamine, and trimer triamine.

[0031] In the bonding paste of the present disclosure, the content of the compound (C) is preferably 0.05 to 2.0 mass %, more preferably 0.1 to 1.0 mass %, based on the mass of the metal particles (A) from the viewpoints of initial bonding strength and thermal cycle properties.

[0032] <Compound (D)> The joining paste of the present disclosure may contain a compound (D) (hereinafter referred to as compound (D)) having at least one type of nitrogen atom selected from the group consisting of secondary nitrogen atoms and tertiary nitrogen atoms and having four or more hydroxyl groups. From the viewpoint of bonding strength and thermal cycle properties, the compound (D) preferably has a tertiary nitrogen atom. The number of tertiary nitrogen atoms is preferably 1 to 3, more preferably 2 to 3. When the number of tertiary nitrogen atoms is 2 or more, the bondability with the metal particles (A) is enhanced, and dispersibility is significantly improved. In addition, the tertiary nitrogen atom has a function of reducing the metal particles (A) and the bonded portion, and when the number of tertiary nitrogen atoms is 2 or more, the reducing function is enhanced. From the viewpoints of dispersibility and reducing function, the number of hydroxyl groups in the compound (D) is preferably 4 to 6. In particular, hydroxyl groups have excellent bonding properties with metal particles (A), and therefore tend to improve dispersibility, and when the number of hydroxyl groups is 4 or more, the bonding properties with metal particles (A) are enhanced, and dispersibility is significantly improved. Furthermore, hydroxyl groups have the function of reducing metal particles (A) and the bonded portions, and when the number of hydroxyl groups is 4 or more, the reducing function is significantly improved.

[0033] The content of the compound (D) is preferably 0.02% by mass or more based on the mass of the metal particles (A). If it is 0.02% by mass or more, the dispersibility of the metal particles (A) is improved, and sintering proceeds with the compound (D) remaining in the coating film, and the coating film has fluidity, so that the adhesion to the bonded part and the defects of the bonding layer are reduced. From the viewpoints of dispersibility, adhesion to the bonded part, and the reduction of defects in the bonding layer, it is more preferably 0.05% by mass or more, and even more preferably 0.10% by mass or more. The content of the compound (D) is preferably 2.00% by mass or less based on the mass of the metal particles (A). By being 2.00% by mass or less, the amount remaining in the coating film after sintering can be reduced, and the bonding strength and thermal cycle properties are excellent. From the viewpoint of reducing the amount remaining, it is more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less.

[0034] <Production of bonding paste> The bonding paste of the present disclosure may contain at least metal particles (A) and a dispersion medium (B), and the manufacturing method thereof is not particularly limited, and it can be prepared using a known method. Examples of devices for preparing the bonding paste from the metal particles (A) and the dispersion medium (B) include a disperser, a three-roll mill, a bead mill, an ultrasonic disperser, and a self-revolving mixer.

[0035] The mass ratio of the metal particles (A) based on the mass of the bonding paste is preferably 80% by mass to 95% by mass, more preferably 85% by mass to 94% by mass. By including the metal particles (A) in the above range, the bonding paste exhibits good printability, while suppressing the residual of the dispersion medium (B) in the bonded body and suppressing the generation of voids derived from the dispersion medium (B), thereby exhibiting good bonding strength.

[0036] The bonding paste of the present disclosure may contain additives, such as a sintering accelerator, a binder resin, a resin-type dispersant, a reducing agent, and the like.

[0037] <Jointed body and method for manufacturing the joined body> The bonding paste of the present disclosure can bond a first bonded part and a second bonded part to obtain a bonded body. The bonded body can be manufactured, for example, by the following manufacturing method (I) using pressureless bonding or manufacturing method (II) using pressure bonding. The bonding paste of the present disclosure has a controlled weight loss during sintering, and can suppress voids in the coating film after sintering even under pressureless conditions, thereby achieving high thermal conductivity. In addition, the bonding strength is excellent, and the decrease in bonding strength due to thermal cycles can be suppressed.

[0038] [Manufacturing method (I)] The manufacturing method (I) is a pressureless bonding method, and preferably includes, for example, the following steps (1) to (3). (1) A step of applying a bonding paste to a first object to be bonded. (2) A step of placing a second part to be joined on the first part to be joined that has been applied with the joining paste. (3) A step of sintering the laminated body in a pressureless environment.

[0039] (1) Coating process The method of applying the bonding paste to the object to be bonded is not particularly limited as long as it can be applied uniformly to the member, and examples thereof include various printing methods such as screen printing, flexographic printing, offset printing, gravure printing, metal mask printing, gravure offset printing, and the like, and a discharge method using a dispenser, etc. The bonding paste of the present disclosure has excellent fluidity even when it contains metal particles at a high concentration, and is therefore particularly preferably used in combination with metal mask printing.

[0040] (2) Placement process Next, a second part to be joined is placed on the first part to be joined to which the joining paste of the present disclosure has been applied. When the joining paste of the present disclosure is used, the second part to be joined can be placed without applying pressure. In the pressure-free joining, the placing step is preferably also performed without applying pressure, but it is also possible to place the second part to be joined while applying pressure. When applying pressure, the pressure is appropriately set depending on the viscosity of the joining paste and the drying state of the paste, and is preferably 0.001 to 40 MPa, more preferably 0.003 to 30 MPa.

[0041] (3) Sintering process The sintering conditions for pressureless bonding of a laminate in which a second bonded portion is placed on a first bonded portion may be appropriately changed, and may include, for example, conditions of 200 to 350°C under atmospheric pressure, in a nitrogen atmosphere, in a vacuum, or in a reducing atmosphere. Examples of the sintering device include a hot air oven, a sintering furnace, an electric furnace, an infrared oven, a reflow oven, a microwave oven, a hot plate, and an optical sintering device. These devices may be used alone or in combination as appropriate. The pressureless sintering conditions are preferably such that the temperature is raised to a set temperature by measuring the temperature rise at 2°C to 30°C / min, and then the temperature is maintained at or above the set temperature for about 10 minutes to 2 hours. The set temperature is preferably 200 to 350°C, more preferably 230°C to 300°C, and even more preferably 250 to 280°C.

[0042] (2a) Pre-drying process In the manufacturing method (I) using pressureless bonding, it is preferable to provide a pre-drying step (2a) between steps (2) and (3) for the purpose of removing organic components in the bonding coating film. Since the bonding paste of the present disclosure contains the compound (B), the coating film can flow and form a bonding interface even after the dispersion medium (B) has been dried and removed in advance, so a pre-drying step can be provided. By providing a pre-drying step, the residual dispersion medium (B), which is one of the causes of defects (voids) in the bonding layer, can be suppressed, and the bonding layer has excellent density, which is preferable. The preliminary drying can be carried out, for example, using an apparatus similar to the calcination apparatus at a temperature in the range of 60 to 220° C. for 1 to 300 minutes, preferably at a temperature in the range of 70 to 100° C. for 30 to 120 minutes.

[0043] That is, the production method (I) is particularly preferably one comprising the following steps: (1) A step of applying a bonding paste to a first object to be bonded. (2) A step of placing a second part to be joined on the first part to be joined that has been applied with the joining paste. (2a) A step of pre-drying the placed laminate by heating. (3) A step of sintering the laminated body in a pressureless environment.

[0044] [Manufacturing method (II)] The manufacturing method (II) is a method using pressure bonding, and preferably includes, for example, the following steps (10) to (30). (10) applying a bonding paste to the first object to be bonded; (10a) A step of pre-drying the coated laminate by heating. (20) A step of placing a second part to be joined on a first part to be joined that has been coated with a joining paste and pre-dried. (30) A step of sintering the placed laminate in a pressurized environment.

[0045] (10) Coating process The method of applying the bonding paste to the object to be bonded is not particularly limited as long as it can be applied uniformly to the member, and examples thereof include various printing methods such as screen printing, flexographic printing, offset printing, gravure printing, metal mask printing, gravure offset printing, and the like, and a discharge method using a dispenser, etc. The bonding paste of the present disclosure has excellent fluidity even when it contains metal particles at a high concentration, and is therefore particularly preferably used in combination with metal mask printing.

[0046] (10a) Pre-drying process In the manufacturing method (II) using pressure bonding, a pre-drying step (10a) can be provided between steps (10) and (20) for the purpose of removing organic components in the bonding coating film. By providing the pre-drying step, the pre-drying can be carried out, for example, using an apparatus similar to a baking apparatus at a temperature in the range of 60 to 220°C for 1 to 300 minutes.

[0047] (20) Placement process Next, a second part to be joined is placed on the first part to be joined that has been coated with the joining paste of the present disclosure and pre-dried. In the case of pressurized joining, the placing step may also be performed under pressure. The pressure is appropriately set depending on the viscosity of the joining paste and the drying state of the paste, but is preferably 0.1 to 40 MPa, more preferably 0.3 to 30 MPa.

[0048] (30) Sintering process The sintering conditions for pressure bonding a laminate in which a second bonded part is placed on a first bonded part may be changed as appropriate, but examples of such conditions include atmospheric pressure, a nitrogen atmosphere, a vacuum, or a reducing atmosphere at 200 to 350°C. The pressure is appropriately set depending on the viscosity of the bonding paste and the drying state of the paste, but is preferably 0.1 to 40 MPa, and more preferably 1 to 30 MPa.

[0049] In either manufacturing method, the thickness of the bonding layer formed when the bonded parts are bonded with the bonding paste is not limited, and the thickness of the bonding layer is preferably 3 μm to 500 μm, more preferably 10 μm to 200 μm, and even more preferably 20 μm to 100 μm.

[0050] [Part to be joined] The type of the bonded part is not particularly limited, and examples thereof include metal materials, semiconductor materials, plastic materials, ceramic materials, and electronic elements. Examples of metals include copper, gold, and aluminum. Examples of semiconductor materials include silicon, germanium, gallium arsenide, gallium phosphide, cadmium sulfide, silicon nitride, graphite, yttrium oxide, magnesium oxide, silicon carbide, and gallium nitride. Examples of plastic materials include polyimide, polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, and polyethylene naphthalate. Examples of ceramic materials include glass and silicon. Examples of electronic elements include semiconductor elements, LED elements, and power device elements.

[0051] The first and second joined parts may be of different types or may not be the same type. The surfaces of the joined parts may be subjected to a corona treatment, a plating treatment, or the like in order to increase the joining strength of the joined parts. The bonding paste of the present disclosure can reduce voids and achieve strong bonding, and can achieve high thermal conductivity, excellent bonding strength, and thermal cycle properties even for substrates that have not been treated by corona treatment, plating treatment, etc. (also called untreated substrates or plating-less substrates.) For example, the bonding paste of the present disclosure is suitable for a case where the first bonded portion is an untreated substrate (e.g., an untreated copper substrate). In addition, the bonding paste of the present disclosure can reduce voids and achieve strong bonding, and can achieve high thermal conductivity, excellent bonding strength, and thermal cycle characteristics even in a configuration such as "copper base material / bonding layer containing silver particles / SiC element" that is prone to distortion during thermal cycle testing. For example, the bonding paste of the present disclosure is suitable when the second bonded part is SiC. EXAMPLES

[0052] Hereinafter, the present disclosure will be described in detail using examples and comparative examples, but the technical scope of the present disclosure is not limited thereto. In the examples, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified. Numerical values ​​in tables represent "parts" unless otherwise specified.

[0053] [Weight reduction] The weight loss of the bonding paste of the present disclosure was measured using a thermogravimetric differential thermal analyzer (TG / DTA8122 (manufactured by RIGAKU)) by heating 10 mg of a sample in a nitrogen atmosphere from a starting temperature of 30°C to 650°C at a heating rate of 3°C / min. When the weight loss at 650°C, M650, was taken as 100, the weight loss at 150°C was taken as M150, the weight loss at 200°C was taken as M200, the weight loss at 250°C was taken as M250, and the weight loss at 300°C was taken as M300.

[0054] <Production of metal particles> (Production example 1) Metal particles A1 Under a nitrogen atmosphere, 200 parts of toluene and 22.3 parts of silver hexanoate were mixed while stirring at 25°C to obtain a 0.5M solution, and then 1.6 parts of diethylaminoethanol and 0.28 parts of oleic acid were added as a dispersant and dissolved. Then, 73.1 parts of a 20% aqueous solution of succinic acid dihydrazide (hereinafter, SUDH) was added dropwise as a reducing agent, and the liquid color changed from light yellow to dark brown. The temperature was raised to 40°C to promote the reaction. After standing and separating, the aqueous phase was removed to remove excess reducing agent and impurities, and distilled water was added to the toluene layer several times, washing and separation were repeated, and then the process of adding toluene, centrifuging, and removing the supernatant was repeated twice. The precipitate was dried to obtain metal particles A1 in which silver particles were coated with hexanoic acid and oleic acid. The particle size of metal particles A1 was determined by the method described below, and d50 was 210 nm.

[0055] (Production example 2) Metal particles A2 Metal particles A2 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 1.8 parts and the amount of oleic acid was 0.31 parts. The d50 was 185 nm.

[0056] (Production example 3) Metal particles A3 Metal particles A3 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 1.2 parts and the amount of oleic acid was 0.18 parts. The d50 was 290 nm.

[0057] (Production example 4) Metal particles A4 Metal particles A4 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 1.0 part and the amount of oleic acid was 0.14 part. The d50 was 390 nm.

[0058] (Production example 5) Metal particles A5 Metal particles A5 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 2.4 parts and the amount of oleic acid was 0.42 parts. The d50 was 120 nm.

[0059] (Production example 6) Metal particles A6 Metal particles A6 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 0.7 parts and the amount of oleic acid was 0.12 parts. The d50 was 450 nm.

[0060] (Production example 7) Metal particles A7 Metal particles A7 were obtained in the same manner as in Production Example 1, except that the silver hexanoate was replaced with 17.0 parts of copper pentanoate, the amount of diethylaminoethanol was 1.8 parts, and the amount of oleic acid was 0.45 parts. The d50 was 150 nm.

[0061] (Production example 8) Metal particles A10 Metal particles A10 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 2.1 parts and the amount of oleic acid was 0.71 parts. The d50 was 85 nm.

[0062] (Production example 9) Metal particles A11 Metal particles A11 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 1.4 parts and the amount of oleic acid was 0.09 parts. The d50 was 600 nm.

[0063] (Production example 10) Metal particles A12 Metal particles A12 were obtained in the same manner as in Production Example 1, except that the amount of diethylaminoethanol was 0.6 parts and the amount of oleic acid was 0.07 parts. The d50 was 1100 nm.

[0064] [Method for measuring the average particle size of metal particles] Isopropyl alcohol was added to each metal particle and dispersed by an ultrasonic disperser to obtain a 0.5 mass% dispersion. The particle diameter of the metal particles in the obtained dispersion was measured using Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) to obtain the average particle diameter (d50). Among the metal particles produced by the above method, metal particles A1-A7 correspond to the metal particles (a) of the present disclosure, and metal particles A10-A12 correspond to metal particles other than the metal particles (a).

[0065] <Dispersion medium (B)> The following materials were used as the dispersion medium (B). The manufacturer's name, supplementary information, and boiling point are given in parentheses. Dispersion medium B1: Triethylene glycol monobutyl ether (glycol ether type, containing hydroxyl group, boiling point 278°C) Dispersion medium B2: Tersolve TOE-100 (manufactured by Nippon Terpene Chemical Co., Ltd., terpene-based, hydroxyl group-containing, boiling point 268°C) Dispersion medium B3: 1,6-diacetoxyhexane (Tokyo Chemical Industry Co., Ltd., no hydroxyl group, boiling point 260°C) Dispersion medium B4: Dihydroterpineol (manufactured by Nippon Terpene Chemical Co., Ltd., terpene type, containing hydroxyl group, boiling point 210°C) Dispersion medium B5: Diethylene glycol monomethyl ether (glycol ether type, containing hydroxyl group, boiling point 193°C) Dispersion medium B6: Tersolve MTPH (manufactured by Nippon Terpene Chemical Co., Ltd., terpene-based, hydroxyl group-containing, boiling point 308°C)

[0066] <Compound (C)> Compound C1: Pripol 2033 (manufactured by Croda Japan Co., Ltd., a dimer diol having 36 carbon atoms. It consists of two hydroxyl groups and a divalent hydrocarbon group having a branched and cyclic structure. Liquid) Compound C2: Priamine 1071 (manufactured by Croda Japan Co., Ltd., a mixture of a dimer diamine having 36 carbon atoms (composed of two amino groups and a divalent hydrocarbon group having a branched and cyclic structure, liquid) and a trimer triamine having 54 carbon atoms (composed of three amino groups and a trivalent hydrocarbon group having a branched and cyclic structure, liquid)) Compound C3: Pripol 1009 (manufactured by Croda Japan Co., Ltd., hydrogenated dimer acid having 36 carbon atoms. Consists of two carboxyl groups and a divalent hydrocarbon group having a branched and cyclic structure. Liquid at 25°C) Compound C4: Pripol 1040 (manufactured by Croda Japan Co., Ltd., a trimer acid having 54 carbon atoms. It consists of three carboxyl groups and a trivalent hydrocarbon group having a branched and cyclic structure. It is liquid at 25°C.)

[0067] <Compound (D)> Compound D1: Alkanolamine (4 hydroxyl groups, 2 tertiary nitrogen atoms)

[0068] <Production of bonding paste> [Example 1] Metal particles A1 (88 parts) and triethylene glycol monobutyl ether (12 parts) were mixed using a planetary stirrer to prepare a bonding paste.

[0069] [Examples 2 to 29, Comparative Examples 1 to 6] A joining paste was obtained in the same manner as in Example 1, except that the types of materials and the amounts (parts) of the materials were changed according to the compositions shown in Tables 1 to 3. In the tables, blank spaces indicate that no material was added.

[0070] <Evaluation of bonding paste> Using the obtained bonding paste, bonded bodies were produced by the manufacturing methods described in Tables 1 to 3. Note that, in Examples 1 to 27 and Comparative Examples 1 to 6, the following manufacturing method 1 was used, in Example 28, the following manufacturing method 2 was used, and in Example 29, the following manufacturing method 3 was used. Details of the manufacturing methods and printing conditions for the bonding paste are as follows. [Printing conditions (metal mask printing)] Metal mask: opening 7.5 mm square, plate thickness 100 μm (manufactured by Celia Corporation) Metal squeegee: 40mm x 250mm, thickness 1mm (manufactured by Seria Corporation)

[0071] [Manufacturing method 1] The bonding paste was printed once under the above printing conditions on the first bonded part (copper base material (plating-free): 20 mm × 20 mm × 3 mm), and then the plated surface of the second bonded part (gold-plated SiC element: 8 mm × 8 mm × 0.3 mm) was placed with the bonding paste surface facing the bonding paste surface, and bonded without pressure under the sintering condition 1 described below to obtain bonded bodies. [Sintering condition 1] The laminate was placed in a sintering furnace with a nitrogen atmosphere, and the temperature was increased from 25°C to 80°C at a rate of 5°C / min, and pre-dried at 80°C for 90 minutes. After that, the temperature was increased to 300°C at a rate of 8°C / min, and after reaching 300°C, it was held at 300°C for 2 hours.

[0072] [Manufacturing method 2] The bonding paste was printed once on the first bonded part (copper base material (plating-free): 20 mm x 20 mm x 3 mm) under the above printing conditions, and then the plated surface of the second bonded part (gold-plated SiC element: 8 mm x 8 mm x 0.3 mm) was placed facing the bonding paste surface, and bonded without pressure under the sintering conditions described below to obtain a bonded body. [Sintering condition 2] The laminate was placed in a sintering furnace in a nitrogen atmosphere, and the temperature was raised from 25°C to 300°C at 8°C / min. After reaching 300°C, it was held at 300°C for 2 hours.

[0073] [Manufacturing method 3] The bonding paste was printed once on the first bonded part (copper base material (plating-free): 20 mm × 20 mm × 3 mm) under the above printing conditions, and then placed in a hot air oven and pre-dried for 10 minutes at 180°C. Next, the plated surface of the second bonded part (gold-plated SiC element: 8 mm × 8 mm × 0.3 mm) was placed facing the pre-dried bonding paste surface, and pressure-bonded under the following sintering condition 3 to obtain a bonded body. [Sintering condition 3] In a nitrogen atmosphere, a pressure of 30 MPa was applied from above the second bonded part, and the temperature was raised from room temperature to 300°C at a rate of 20°C / min. After reaching 300°C, the same temperature was maintained for 5 minutes.

[0074] The obtained bonded body was used to evaluate the bonding strength and thermal cycle characteristics. In addition, the thermal conductivity was evaluated under the conditions described below. The results are shown in Tables 1 to 3. [Joining strength] The bonded body was fixed at the site of the first bonded part, and pushed toward the second bonded part at a height of 100 μm from the interface between the first bonded part and the bonding layer at a speed of 500 μm / s, and the bond strength (die shear strength) at which the bond was broken was determined and evaluated based on the following evaluation criteria. The higher the die shear strength value, the better, and 10 MPa or more is within the practical range. The measurement conditions are shown below. [Measurement conditions] Measurement equipment: Universal bond tester (Daisi Japan Co., Ltd., 4000 series) Measurement height: 100μm Measurement speed: 500μm / s

[0075] (Evaluation Criteria) S: Die shear strength is 35MPa or more A: Die shear strength is 25MPa or more and less than 35MPa B: Die shear strength is 15MPa or more and less than 25MPa C: Die shear strength is 10MPa or more and less than 15MPa D: Die shear strength is less than 10 MPa

[0076] [Heat cycle characteristics] The bonded body was subjected to the following cycle test, and the bond strength (die shear strength) of the bonded body after the cycle test was measured and evaluated in the same manner as in the above-mentioned [Bonding strength]. A value of 10 MPa or more is within the practical range. [Cycle test] The bonded body was stored at -40°C for 30 minutes, and then at 150°C for 30 minutes, which constituted one cycle. The storage was carried out for 500 cycles.

[0077] [Thermal Conductivity] The thermal conductivity was calculated from the thermal diffusivity, specific heat, and density according to the following formula. Thermal conductivity (W / m K) = density (g / cm 3 ) × specific heat (J / kg K) × thermal diffusivity (mm 2 / s) The thermal diffusivity was determined as follows. The bonding paste was printed once on the first bonded part (copper base material (plating-free): 20 mm × 20 mm × 3 mm) using a metal mask (opening 20 mm square, plate thickness 200 μm) and metal squeegee: 40 mm × 250 mm, thickness 1 mm (manufactured by Ceria Corporation). The second bonded part (copper base material (plating-free): 20 mm × 20 mm × 3 mm) was then placed on the laminate, which was then placed in a sintering furnace in a nitrogen atmosphere and heated from 25 °C to 300 °C at a rate of 8 °C / min. After reaching 300 °C, the laminate was held at 300 °C for 2 hours to obtain a bonded part. The bonded part obtained was coated with carbon using a carbon spray. The thermal diffusivity was then measured using a xenon flash analyzer LFA447 Nano Flash (manufactured by NETZSCH). The higher the thermal conductivity value, the better the product, and a value of 80 W / (m·K) or more is within the practical range.

[0078] (Evaluation Criteria) S :250W / (m·K) or more A: 200W / (m K) or more and less than 250W / (m K) B: 150W / (m K) or more and less than 200W / (m K) C: 80W / (m K) or more and less than 150W / (m K) D: Less than 80W / (m K)

[0079] [Table 1]

[0080] [Table 2]

[0081] [Table 3]

[0082] According to the results in Tables 1 to 3, when the bonding paste of the present disclosure was used, the thermal conductivity and bonding strength were very high, even in configurations in which stable bonding is extremely difficult, such as a pressureless, plating-free substrate and a large-area SiC element, and a decrease in bonding strength was suppressed even after performing a thermal cycle test. In particular, the bonding paste having an M150 / M200 value of 0.975 or more, the bonding paste having 50 mass% or more of a dispersion medium (b1) having a boiling point of 250 to 300°C, the bonding paste in which the dispersion medium (b1) contains at least one selected from the group consisting of terpenes and glycol ethers, the bonding paste having 10 mass% or less of a dispersion medium (b2) having a boiling point of more than 300°C, and the bonding paste having 90 mass% or more of a dispersion medium having a hydroxyl group based on the total mass of the dispersion medium (B) suppressed voids in the coating film after sintering even under pressure-free conditions, exhibited high thermal conductivity, had excellent bonding strength, and suppressed deterioration of the bonding strength due to thermal cycles (Examples 1 and 7, Example 7 and 17, Example 2 and 6, Example 1 and 13, Example 2 and 6). On the other hand, when the bonding paste of the comparative example was used, the thermal conductivity and bonding strength were significantly low, and the bonding strength after the thermal cycle test also decreased significantly.

Claims

1. A bonding paste comprising metal particles (A) and a dispersion medium (B), The metal particles (A) contain metal particles (a) having an average particle diameter of 100 nm or more and 500 nm or less in an amount of 50 mass% or more based on the total mass of the metal particles (A), The metal particles (A) contain silver and / or copper, When the weight loss M650 of the bonding paste at 650°C is taken as 100, the weight loss M200 at 200°C is 88 or more and 98 or less (wherein the weight loss M650 and the weight loss M200 are determined by a thermogravimetric differential thermal analysis method by heating a 10 mg sample in a nitrogen atmosphere at a starting temperature of 30°C and a heating rate of 3°C / min).

2. 2. The joining paste according to claim 1, wherein when the weight loss at 150°C is defined as M150 when the weight loss M650 is defined as 100, the ratio of the weight loss M150 to the weight loss M200 (M150 / M200) is 0.975 or more (wherein the weight loss M150 is determined by a thermogravimetric differential thermal analysis method by heating a 10 mg sample in a nitrogen atmosphere at a starting temperature of 30°C and at a heating rate of 3°C / min).

3. The dispersion medium (B) is, for example, terpineol, dihydroterpineol, dihydroterpinyl acetate, 2-(1-methyl-1-(4-methyl-3-cyclohexenyl)ethoxy)ethanol, isobornylcyclohexanol, texanol, carbitol, carbitol acetate, butylcarbitol, isophorone, γ-butyllactone, dipropylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol methyl-n-propyl ether, 3-methoxy-3-methylbutyl acetate, ethylene glycol, propylene glycol diacetate, dipropylene glycol methyl ether acetate, 1,3 The bonding paste according to claim 1, which contains at least one selected from the group consisting of -butylene glycol, 1,3 butanediol, 1,4 butanediol, 2-ethyl 1,3 hexanediol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, triethylene glycol monoethyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, polyethylene glycol monobutyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, and isoparaffin-based dispersion media.

4. The dispersion medium (B) has a content of a dispersion medium (b1) having a boiling point of 250 ° C. or more and 300 ° C. or less, based on the total mass of the dispersion medium (B). The joining paste according to claim 1.

5. The bonding paste according to claim 4 , wherein the dispersion medium (b1) contains at least one selected from the group consisting of terpenes and glycol ethers.

6. The joining paste according to claim 1, wherein the content of the dispersion medium (b2) having a boiling point exceeding 300° C. in the dispersion medium (B) is 10 mass% or less based on the total mass of the dispersion medium (B).

7. The bonding paste according to claim 1 , wherein the dispersion medium (B) has a content of a dispersion medium having a hydroxyl group of 90 mass % or more based on the total mass of the dispersion medium (B).

8. A bonded body in which a first bonded part and a second bonded part are bonded with the bonding paste according to claim 1.

9. The bonded body according to claim 8 , wherein the first bonded portion is an untreated substrate.

10. The bonded body according to claim 8 or 9, wherein the second bonded portion is made of SiC.

Citation Information

Patent Citations

  • Joint material and joining method

    JP2020164895A

  • Joining paste, junction body using the same, and method of making junction body

    JP2021098875A

  • Joining material, joining-material producing method, and joining method

    JP2022003161A

  • Metal particle-containing composition, paste for joining, joined body, and production method of joined body

    JP2022099238A

  • Composition for bonding

    WO2013061527A1